2016
DOI: 10.1007/s10935-016-0456-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Current Smoking Among Off-Reserve First Nations and Métis Youth: Results From the 2012 Aboriginal Peoples Survey

Abstract: First Nations and Métis, two of Canada's constitutionally recognized Indigenous groups, suffer from poorer overall health than non-Indigenous Canadians. Current smoking, a known predictor of chronic health conditions, is close to twice as prevalent among Indigenous youth as it is among non-Indigenous Canadian youth. However, little population-level research has examined the correlates of current smoking among this population. Guided by a health framework centered on Indigenous-specific determinants, we used da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The association between smoking and household income was in the right direction for the other two groups of students. These findings are in line with the well-known associations between teen smoking and family socio-economic characteristics (Hanson & Chen, 2007;Ryan et al, 2017;Shields, 2005b;Soteriades & DiFranza, 2003;Wen et al, 2009;Wiium & Wold, 2009). Future studies are necessary to better understand why youth from low-income families may be more likely to smoke.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The association between smoking and household income was in the right direction for the other two groups of students. These findings are in line with the well-known associations between teen smoking and family socio-economic characteristics (Hanson & Chen, 2007;Ryan et al, 2017;Shields, 2005b;Soteriades & DiFranza, 2003;Wen et al, 2009;Wiium & Wold, 2009). Future studies are necessary to better understand why youth from low-income families may be more likely to smoke.…”
Section: Discussionsupporting
confidence: 82%
“…Past research has shown an association between smoking and frequent participation in extracurricular sport activities among off-reserve Indigenous youth (Ryan et al, 2017). In this study, we paid attention to extracurricular activities that were organized specifically by schools and, in this context, participation in school-based club activities was associated with a lower prevalence of smoking among Métis students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I identified eight quantitative studies on the health of Indigenous youth in Canada (Ng et al 2010;Elton-Marshall et al 2013;Kaspar 2013;Ryan et al 2016a;Ryan et al 2016b;Bhawra et al 2017;Van Bewer and Woodgate 2017;Nasreen et al 2018). All of these studies focus on negative outcomes from smoking, heavy drinking and obesity to violence in school and mental illness.…”
Section: Forewordmentioning
confidence: 99%